Resonance raman spectroscopy of the heme groups of cytochrome cbb3 in hodobacter sphaeroides - Babcock, Gerald T.; García-Horsman, Juan Arturo; Varotsis, Constantinos (My University, 1995)
Resonance Raman spectra are reported on ferric, ferrous, and cyanide-bound cytochrome cbb3 oxidase, and compared with other heme b and heme c containing enzymes. These spectra are used to assess the spin and ligation states of the hemes via the porphyrin marker band frequencies, and for the deoxy form of heme b3, the status of the Fe-histidine bond via its stretching frequency. The cytochrome cbb3 complex in its resting form contains six-coordinated low-spin hemes, c, a six-coordinated low-spin heme b, and a six-coordinated high-spin heme b3. In the reduced form of the enzyme, heme b3 is five-coordinated and high-spin, while hemes c and heme b remain six-coordinated and low-spin. The cyanide-bound spectrum is consistent with low-spin six-coordinated heme b3. Our results indicate that the 235 cm-1 mode observed in the reduced spectrum of cbb3 can be assigned to the Fe2+-His of heme b3. The v(Fe2+-His) frequency is the highest among those reported to date for the heme-copper respiratory oxidases. Possible explanations for the atypical Fe-His bonding are discussed
Keywords: Raman spectroscopy; Heme; Cytochrome oxidase; Enzymes; Copper; Porphyrins